2017
DOI: 10.1002/2016wr020198
|View full text |Cite
|
Sign up to set email alerts
|

Suspended sediment and turbidity after road construction/improvement and forest harvest in streams of the Trask River Watershed Study, Oregon

Abstract: Transport of fine‐grained sediment from unpaved forest roads into streams is a concern due to the potential negative effects of additional suspended sediment on aquatic ecosystems. Here we compared turbidity and suspended sediment concentration (SSC) dynamics in five nonfish bearing coastal Oregon streams above and below road crossings, during three consecutive time periods (“before”, “after road construction/improvement”, and “after forest harvest and hauling”). We hypothesized that the combined effects of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 84 publications
0
9
1
Order By: Relevance
“…The lack of increase in stream particulate THg and MeHg or TSS concentrations in clear-cut catchments is in contrast to what has been observed in other studies, where logging has been shown to increase catchment erosion and suspended sediment concentrations. , The absence of a response of these parameters in our study may result from the forestry BMPs that were used to reduce erosion, such as limiting new road construction, effective use of road prism drainage techniques, using cable logging where the felled trees are moved across the site suspended by a cable, and the practice of leaving a thick layer of slash materials covering the soil after harvesting. , These BMPs are widely utilized as part of forestry operations in the US and elsewhere; however, it is also not uncommon for slash to be removed or burned on-site. The removal of woody biomass, including stump harvesting, has gained interest in recent years for use as a renewable fuel or other products. , As such, the results from our study are believed to be representative of commonly applied contemporary forestry techniques; however, forestry operations not utilizing these BMPs may have larger influence on Hg mobilization and other water quality end points.…”
Section: Results and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of increase in stream particulate THg and MeHg or TSS concentrations in clear-cut catchments is in contrast to what has been observed in other studies, where logging has been shown to increase catchment erosion and suspended sediment concentrations. , The absence of a response of these parameters in our study may result from the forestry BMPs that were used to reduce erosion, such as limiting new road construction, effective use of road prism drainage techniques, using cable logging where the felled trees are moved across the site suspended by a cable, and the practice of leaving a thick layer of slash materials covering the soil after harvesting. , These BMPs are widely utilized as part of forestry operations in the US and elsewhere; however, it is also not uncommon for slash to be removed or burned on-site. The removal of woody biomass, including stump harvesting, has gained interest in recent years for use as a renewable fuel or other products. , As such, the results from our study are believed to be representative of commonly applied contemporary forestry techniques; however, forestry operations not utilizing these BMPs may have larger influence on Hg mobilization and other water quality end points.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…41,54 The absence of a response of these parameters in our study may result from the forestry BMPs that were used to reduce erosion, such as limiting new road construction, effective use of road prism drainage techniques, using cable logging where the felled trees are moved across the site suspended by a cable, and the practice of leaving a thick layer of slash materials covering the soil after harvesting. 42,55 These BMPs are widely utilized as part of forestry operations in the US and elsewhere; however, it is also not uncommon for slash to be removed or burned on-site. The removal of woody biomass, including stump harvesting, has gained interest in recent years for use as a renewable fuel or other products.…”
Section: Forest Harvesting Impacts On Particulate Mercurymentioning
confidence: 99%
“…As a result, current forest management has been designed to mitigate sediment delivery and minimize negative effects on aquatic and riparian ecosystems. Sediment delivery to streams under contemporary forest management can be very different from what was documented in past studies of historical management practices (Loehle et al, 2014;Arismendi et al, 2017). However, little is known about the consistency of fine sediment transport among neighboring watersheds, leaving questions about how sediment transport in streams varies spatially and temporally under contemporary forest management.…”
Section: Fine Sediment Studymentioning
confidence: 87%
“…5 Furthermore, recent increases in urbanization and industrialization, in order to meet the requirements of an ever-growing population, have resulted in an increasing pace of constructional activities, which has had a significant negative impact on the water quality of many natural water bodies. 6 The current study aims to characterize the impact of road operations on local surface water sources, as well as to evaluate the impact of spatial variation associated with road pollutants on water quality and to investigate the relationship between various water quality parameters and seasons. The investigation's findings contributed in determining the extent to which water quality has deteriorated as a result of vehicular emission and other activities on road.…”
Section: Introductionmentioning
confidence: 99%